2017
DOI: 10.1016/j.ijpsycho.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and threat imagery manipulates heart rate and anxiety responses to stress

Abstract: This study investigated the influence of different types of mental imagery on heart rate and anxiety responses to a standard psychological stress task. Using a within-design, 25 females (M=23.24; SD=4.19) imaged three different scripts (challenge, threat, and neutral) to manipulate appraisal of a speech preparation task. Following each script, participants completed the task. Heart rate was recorded during a resting baseline prior to each imagery script and during each speech preparation task. Cognitive and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
3
22
3
Order By: Relevance
“…Further, participants reported that during the imagery task, they felt the emotions of the image ( M = 4.70 out of 7, SD = 1.10) and used the image ( M = 5.25 out of 7, SD = 0.96) for the duration of the task. Our participants showed slightly higher ease of imaging compared to participants in a study by Williams et al (2017); M = 4.05 out of 7 in stress condition who used a similar scale to assess participant’s ease of imaging a stressful imaging task. Consideration of participants’ physiological and self-reported responses suggest that the imagery induction successfully induced a stress response in the expected directions.…”
Section: Resultscontrasting
confidence: 47%
“…Further, participants reported that during the imagery task, they felt the emotions of the image ( M = 4.70 out of 7, SD = 1.10) and used the image ( M = 5.25 out of 7, SD = 0.96) for the duration of the task. Our participants showed slightly higher ease of imaging compared to participants in a study by Williams et al (2017); M = 4.05 out of 7 in stress condition who used a similar scale to assess participant’s ease of imaging a stressful imaging task. Consideration of participants’ physiological and self-reported responses suggest that the imagery induction successfully induced a stress response in the expected directions.…”
Section: Resultscontrasting
confidence: 47%
“…Concerning the connection with trait-anxiety, it is negative in both categories of sports, showing greater strength in individual sports. These data can be explained by Ros et al [ 67 ] in that instructions that emphasize the idea that emotional intelligence is an ability which can be learnt with the aim of controlling fundamental emotions in the sports context, such as stress, aggressiveness or anxiety, the latter being a disturbing element that deteriorates sport performance [ 52 , 68 ]. In collective sports, emotional intelligence rises and the levels of trait-anxiety fall; this is explained by the fact that in this category of sports, pressure endured by athletes during training sessions and competitions is distributed between members of the team [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates findings from studies of individual and collective sports. Ros et al [76] identified that emotional intelligence allows athletes to adopt an orientation towards the task, increasing their focus on personal improvement, enabling them to reduce their anxiety levels [77]. Moreover, higher emotional intelligence enables participants to better understand the stressors which produce a negative emotional state, thus enabling them to avoid these stressors and avoid high state anxiety [76].…”
Section: Discussionmentioning
confidence: 99%